New antiarrhythmic drugs for atrial fibrillation. Issue 3 (September 2016) - Fragakis, N.; Vassilikos, V. P.
Abstract : Abstract: Atrial fibrillation is a complex arrhythmia that is difficult to treat with conventional antiarrhythmic agents. Novel pharmacological approaches are in progress focused on the development of agents with selective affinity to ion channels predominately involved in the atrium. In parallel, research efforts have been focused on the development of agents targeting to modification of those pathways and molecular mediators which are involved in the propagation and maintenance of atrial fibrillation (AF). In this review, we focus on the basic and clinical pharmacology of new and emerging antiarrhythmic drugs such as vernakalant, dronedarone, and ranolazine, whereas we briefly comment on the future directions of antiarrhythmic therapy in AF. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/4469486/Activity.aspx